Religieux Costumes. French book plate lithograph Religious historical... - Unsigned artwork... (Wikimedia Commons, 1910)
Notice visuelle issue de Wikimedia Commons pour la demo du fonds documentaire.
Droits : Licence Creative Commons Attribution 4.0 via Wikimedia Commons
Keywords: Histoire; iconographie; gravure; photographie; Wikimedia Commons; Iconographie